ASPECT-R—A Tool to Rate the Pragmatic and Explanatory Characteristics of a Clinical Trial Design - Alphs, Larry D. (Innov Clin Neurosci, 2016)
Objective: Clinical and observational trials can be broadly categorized into having explanatory or pragmatic approaches with specific trial designs located somewhere along this spectrum. Two 10-domain instruments, the PRECIS and Pragmascope, have been developed to facilitate clinical trial design within a framework that is either more explanatory or pragmatic. Design: We have adapted the PRECIS and Pragmascope instruments to permit both design support and post-hoc evaluation of clinical trials and to improve consistency of use and interpretation across raters. This adapted instrument, A Study Pragmatic-Explanatory Characterization Tool-Rating—or ASPECT-R—is described. Results: Adaption of the PRECIS and Pragmascope instruments included reducing the 10 original domains to six. Each of the six ASPECT-R domains has a definition of domain terminology and detailed descriptive anchors. The domains are rated from 0 to 6, where 0 is considered extremely explanatory and 6 extremely pragmatic. Using an Excel®-based file with cover page cells for entry of the study objective(s) and study population of interest, the ASPECT-R instrument has individual domain-related worksheets where the user rates each of the six domains. Each of the six domain worksheets has a section provided for the user to summarize and record the rationale for their domain scoring. Each domain worksheet page also contains a radar graph that auto-populates each of the domain ratings as the user completes these ratings. Conclusion: This new tool, ASPECT-R, should provide a reliable, objective way to rate studies along the explanatory-pragmatic spectrum that will better support trial design and facilitate interpretation of completed trials. The complete ASPECT-R tool and guide materials can be accessed online by clicking or visiting this link: http://innovationscns.com/aspect-r-tool-and-training-materials/.